Field reaction of ginger germplasm to Phyllosticta zingiberi - and JOHNSON K. GEORGE, T. G. NAGESHWAR RAO, B. SASIKUMAR (Indian Phytopathology, 2002)
Ginger germplasm accessions (100) were evaluated for their reaction and tolerance to P. zingiberi leaf spot under field conditions at the Research Farm, Peruvannamuzhi, India. Pieces of ginger rhizome (4 from each accession) were sown in 45 cm diam.cement pots outdoors in May-Jun. 1990 and 1991. As the disease was already present in the area, incidence was recorded without artificial inoculation. A scale was devised to score severity of symptoms of infection in the affected plants. This data was then used to create a disease index table for the 100 accessions. It was found that 11 accessions were tolerant (disease index < mean-SD) and a further 42 were moderately tolerant.